Manajemen Strategi Kepala Sekolah Dalam Pengembangan Kompetensi Profesional Guru - Aditia Permana; Dedi Djubaedi; Dewi Cahyani (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Principal Strategic Management in Developing Teachers' Professional Competence This study aimed to describe the principal's strategic management in developing teachers' professional competence to improve educational quality at SMP Islam Al Azhar 5 Cirebon. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation involving the principal, vice principal, teachers, and school documents. The data were analyzed through data reduction, data display, and conclusion drawing, while trustworthiness was strengthened through source and technique triangulation. The findings showed that strategic planning was conducted through teacher needs analysis, performance evaluation, vision and mission alignment, managerial deliberation, and the design of professional development programs. Strategy implementation was carried out through training, workshops, seminars, teacher subject forums, mentoring, supervision, motivation, facility provision, and work culture strengthening. Strategy evaluation was conducted through direct monitoring, program reflection, and follow-up on teacher achievement. These programs improved content mastery, lesson planning, media use, instructional communication, discipline, and teacher participation in academic and nonacademic activities. The impact was reflected in better learning processes, student achievements, public trust, school accreditation, and stronger educational services. Planned, participatory, and sustainable strategic management by the principal is a key factor in developing teachers' professional competence and improving educational quality.